Respostas

2014-06-26T11:29:24-03:00
(x - 5)² - 8 (x - 5) + 7 = 0
x² - 10x + 25 - 8x + 40 +7 = 0
x² - 18x + 72 = 0
Δ = (-18)² - 4(1)(72)
Δ = 36
x = (-(-18) +/- √36)/2(1)
x' = (18 + 6)/2
x' = 12
x'' = (18 - 6)/2
x'' = 6

Qualquer dúvida, é só falar.
1 5 1
2014-06-26T11:40:22-03:00
X² - 10x + 25 - 8x + 40 +7 = 0
x² - 18x + 72 = 0

x=-b+-√b²-4ac
    ----------------
         2a
x=18+-√(-18)²-4.1.72
    ---------------------
          2.1
x=18+-√324-288
     -----------------
           2
x=18+-√36
     ---------
         2
x=18+-6
   --------
      2
x'=18+6
    -------
       2
x'=24/2=12
x''=18-6
      ------
       2
x''12/2=6
S={12,6}